Arenaviruses bite the “dust” - Gomez, Ricardo Martin (2013)
In this issue of Blood, Loria and colleagues present new aspects on the role of platelets in protecting against both lethal hemorrhagic diathesis and virus replication in viral hemorrhagic fever (VHF), using a murine model of lymphocytic choriomeningitis virus (LMCV) infection1.